2016
DOI: 10.1097/phm.0000000000000407
|View full text |Cite
|
Sign up to set email alerts
|

Radial Extracorporeal Shock Wave Therapy Is Not More Effective Than Placebo in the Management of Lateral Epicondylitis

Abstract: The rESWT does not seem to be more effective either in reducing pain or improving function or grip strength in patients with lateral epicondylitis at least at 3 mos after treatment when compared with sham rESWT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 36 publications
1
24
0
1
Order By: Relevance
“…Another study by Capan et al found no difference between sham and ESWT treatment for lateral epicondylitis [28] . Some studies found ESWT to be superior to placebo whereas other studies found it to be ineffective [9] .…”
Section: Discussionmentioning
confidence: 94%
“…Another study by Capan et al found no difference between sham and ESWT treatment for lateral epicondylitis [28] . Some studies found ESWT to be superior to placebo whereas other studies found it to be ineffective [9] .…”
Section: Discussionmentioning
confidence: 94%
“…Taheri et al, in a clinical trial, comparing low dose and high dose focused ESWT, highlighted similar results in pain reduction especially in the first 3 months [35]. Considering the radial ESWT, not significant advantages were found in efficacy in reducing pain or improving function when compared with sham radial ESWT [36]. Moreover, our study identifies some risk factors to the persistence of the symptomatology such as age, duration of disease, and the performing of ECRB high involving occupation and sports activities, which could prejudice the satisfaction of the therapy, making the recovery longer.…”
Section: Discussionmentioning
confidence: 96%
“…For example, a rESWT regimen that employs 2000 pulses of 10 Hz frequency at a 1.8 bar of air pressure at each session at three once weekly sessions was compared with sham rESWT in a double-blind, randomized, placebo-controlled study. The authors concluded that rESWT does not seem to be effective in patients with lateral epicondylitis (21). On the other hand, another study with different rESWT regimens in which the total number of shocks was 2500, the pressure was 2 bars: 1500 shocks of 5 Hz frequency followed by 500 shocks of 10 Hz frequency were applied locally on the lateral epicondyle and 500 shocks of 2 bars pressure and 5 Hz frequency were compared respectively.…”
Section: Introductionmentioning
confidence: 99%